The organisation of the preventative and curative medical services and hospital and laboratory systems under a Ministry of Health (London : Co-operative Printing Society)
1919 1919 1910s 18 pages with one another, their personnels may be interchangeable, and it must be possible to modify the working details of each unit according to experience and to the needs of the totality. The several activities of this National Health Service should all pivot upon the local hospital as an Institute of Health. ACTIVITIES OF THE NATIONAL HEALTH SERVICE. 1). THE PUBLIC HEALTH SERVICE — This service would continue the work of the existing municipal or county Public Health Services at present administered by the Medical Officers of Health, their assistants, and Inspectors of Food and Nuisances. It would deal largely with material environment and infection, but its personnel, both medical and lay, would require to be largely augmented to render effective the work of carrying out much wider powers which ought to be conferred upon it. All existing laws relating to public health administered by this branch require to be codified, and, where antiquated or defective, amended. 2. THE DOMICILIARY AND NURSING SERVICE — This will direct its attention to the care of expectant and nursing mothers, infants, and young children before school age, and the general care of cases which are usually treated at home. At present this service is incomplete, and every year many thousands of infants die who would otherwise live and become quite healthy citizens, while others grow up ill and stunted to form citizens of low grade health, who often perish from phthisis and other chronic diseases as soon as the strain of employment begins to tell. A complete service of doctors, health visitors, nurses, and midwives working on preventive lines would save a great number of infant lives annually, and prevent the lifelong suffering of mothers from defects acquired at childbirth, and at present neglected. For serious cases, and for part of its clinical work, this Service would have a section of the health centre, where mothers and children would be seen. Uncomplicated cases of labour would be attended by a doctor or a qualified midwife, and instruction in infant feeding and care would be given by the nurses of the branch in the homes, under medical supervision. The mother would be assisted in the work of the house before and after the birth of the infant. This Service would also be one of the chief instructing agencies in the hygiene of the household and the proper care of children. Mothers would be encouraged to seek medical advice from the qualified medical officers of the Service in their own homes, and much latent disease would be detected and checked in early stages. Other practitioners of this Service will render domiciliary treatment as hitherto, but will be enabled, whenever it is deemed expedient, to transfer cases from the home to the health centre for institutional treatment. 3. THE SCHOOL HEALTH SERVICE — This would be organised much on present lines but much more amply provided with trained nurses to undertake treatment under the direction of the doctors. All school children should be taught, as a fundamental part of their education and as a most interesting subject, something authentic about their own bodies and the simple laws of health. To this end all teachers ought to be thoroughly instructed by medical officers of this Service. The environment of the school-room and everything making for health at school should be under the care of this branch. Disease should not merely be inspected and codified; it should be properly treated with all possible speed. More serious cases should be transferred to the hospital service, others should be treated at the school clinic. Schools for tuberculous children and for those suffering from other diseases benefited by open-air treatment should be increased until sufficient to accommodate and give relief to all sufferers. 3 36/H24/6